2013
DOI: 10.1016/j.exer.2013.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Central corneal thickness does not correlate with TonoLab-measured IOP in several mouse strains with single transgenic mutations of matricellular proteins

Abstract: Accurate and reliable measurement of intraocular pressure (IOP) is crucial in the study of glaucoma using the mouse model. The purpose of this study was to determine the relationship between TonoLab-measured IOP and central corneal thickness (CCT) in mouse strains with single gene mutations of matricellular proteins. Wild-type (WT) and transgenic mouse strains with single gene mutations (KO) of thrombospondin-1 (TSP-1), thrombospondin-2 (TSP-2), osteopontin (OPN), hevin, and secreted protein acidic rich in cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…IOP was measured in conscious animals using a rebound tonometer (Tonolab, Colonial Medical Supply). Animals were measured when anaesthetized by intraperitoneal injection of a ketamine/xylazine as described above.…”
Section: Methodsmentioning
confidence: 99%
“…IOP was measured in conscious animals using a rebound tonometer (Tonolab, Colonial Medical Supply). Animals were measured when anaesthetized by intraperitoneal injection of a ketamine/xylazine as described above.…”
Section: Methodsmentioning
confidence: 99%
“…159 These findings were confirmed in a study summarizing IOP changes in all matricellular null strains, which also demonstrated that CCT need not be measured to evaluate IOP differences in these strains (Table 1). 78 Interestingly, aqueous humor turnover rates-as measured by fluorophotometric techniques-are enhanced in both TSP-1-and TSP-2-null mice, suggesting that both may play roles in regulating aqueous outflow facility.…”
Section: Figmentioning
confidence: 99%
“…75,76 Interest in SPARC as a regulator of ECM homeostasis in the TM continues to grow. Our laboratory has shown that SPARC-null mice exhibit 15%-20% lower IOP compared with their wild-type counterparts 77,78 and that these mice demonstrate a more uniform pattern of aqueous humor outflow (Fig. 2).…”
Section: Matricellular Proteins In the Tmmentioning
confidence: 99%
See 2 more Smart Citations